2021
DOI: 10.1101/2021.10.12.464120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

gp130/STAT3 signaling is required for homeostatic proliferation and anabolism in postnatal growth plate and articular chondrocytes

Abstract: Growth of long bones and vertebrae is maintained postnatally by a long-lasting pool of progenitor cells. Little is known about the molecular mechanisms that regulate the output and maintenance of the cells that give rise to mature cartilage. Here we demonstrate that postnatal chondrocyte-specific deletion of a transcription factor Stat3 results in severely reduced proliferation coupled with increased hypertrophy, growth plate fusion, stunting and signs of progressive dysfunction of the articular cartilage. Thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Interestingly, DNMT3B was found to be among a few putative STAT3 binding targets overlapping between development and disease (Figure 4c,d). Upon analyzing the bulk RNA‐sequencing data obtained from STAT3 knocked down fetal chondrocytes (Liu, Lin, Li, Lu, Geng, Zhang, et al, 2022), we observed an increase in expression of DNMT3B (fold change = 2.386, p = 0.01), indicating that STAT3 binding represses transcription of DNMT3B, which is reversed upon STAT3 knock down (Figure 5a). Also, pharmacological activation of STAT3 signaling in adult chondrocytes (Shkhyan et al, 2018) results in significant downregulation of DNMT3B (fold change = −2.43, p = 0.05) (Figure 5b) accompanied with a significant decrease in DNA methylation.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Interestingly, DNMT3B was found to be among a few putative STAT3 binding targets overlapping between development and disease (Figure 4c,d). Upon analyzing the bulk RNA‐sequencing data obtained from STAT3 knocked down fetal chondrocytes (Liu, Lin, Li, Lu, Geng, Zhang, et al, 2022), we observed an increase in expression of DNMT3B (fold change = 2.386, p = 0.01), indicating that STAT3 binding represses transcription of DNMT3B, which is reversed upon STAT3 knock down (Figure 5a). Also, pharmacological activation of STAT3 signaling in adult chondrocytes (Shkhyan et al, 2018) results in significant downregulation of DNMT3B (fold change = −2.43, p = 0.05) (Figure 5b) accompanied with a significant decrease in DNA methylation.…”
Section: Resultsmentioning
confidence: 92%
“…Next, we found that differentially methylated CpGs gained methylation (hypermethylated) in STAT3 knocked down fetal chondrocytes (Figure 3b). Furthermore, we explored the concordance between genes associated with differentially methylated CpGs that gain methylation and genes downregulated (i.e., genes with inaccessible chromatin) in STAT3 knocked down fetal chondrocytes (Liu, Lin, Li, Lu, Geng, Zhang, & Evseenko, 2022) (Figure 3c). The 211 genes obtained from this overlap revealed an association with connective tissue development, extracellular matrix organization, response to oxygen levels, response to ATP, and glycolytic processes (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous data suggested that IL-6 cytokines drive both regenerative and destructive outcomes in synovial joints through selective and context specific activation of signaling residues within the intracellular domain of gp130 receptor (14,23), and are also required for homeostatic maintenance of skeletal progenitors (34)(35)(36)(37)(38). Complete inhibition of gp130 signaling has been attempted previously for several therapeutic indications.…”
Section: Discussionmentioning
confidence: 99%